REDESIGN PAKAIAN SECONDHAND BERWARNA PUTIH MENGGUNAKAN TEKNIK PATCHWORK YANG TERINSPIRASI DARI KAIN POLENG - Yashinta Ferindra (Narada : Jurnal Desain dan Seni, 2020)
Indonesia has a lot of secondhand clothing sales places, one of them is at the Cimol Gedebage Market in Bandung. Some factors are the presence of secondhand clothing because it does not pass QC (Quality control). One type of secondhand clothing is a white shirt and dress because it is easy to get dirty and easy to get stains on clothes that make clothes not in demand again. Therefore Exploration is used to determine the appropriate technique to be applied to white clothing on shirts and dresses that will be reprocessed by redesigning and adding elements with surface textile design and patchwork techniques inspired by Balinese poleng fabric that has an archipelago culture. From this research, hopefully, it can change the mindset of the people in secondhand clothing as clothes that are not suitable for use to be suitable for use.